Experimental study on solid electrolyte interphase of graphite electrode in Li-ion battery by surface analysis technique. (4th March 2018) - Jung, Eun Young; Park, Choon-Sang; Lee, Jae Cheol; Pazhetnov, Egor; Suh, Kwang Jong; Heo, Sung; Hong, Tae Eun; Lee, Dong Ho; Chien, Sung-Il; Tae, Heung-Sik
ABSTRACT: This article investigates the characterization of the solid electrolyte interphase (SEI) on the graphite electrode after long cycling times. The chemical composition, molecular structure, and thickness of SEI layer on graphite electrode are characterized by using scanning electron microscope (SEM), X-ray photoelectron spectroscopy (XPS), auger electron spectroscopy (AES), and time of flight-secondary ion mass spectrometry (ToF-SIMS) with respect to cycling times. In particular, we focus the changes in the properties of SEI layer on the graphite electrode surface between initial-state (after 1 cycle) and aged-state (after 500 cycles). More detailed properties of SEI layer after long cycling times are systematically studied by XPS, AES, and ToF-SIMS.